Valuing executive stock options with endogenous departure - Cuny, Charles J.; Jorion, Philippe (Journal of Accounting and Economics, 1995)
Executive stock options differ from exchange-traded options because of vesting and portability restrictions. Executive departure from the firm forces early exercise, reducing the value of executive options. Current methodology calculates the option value by multiplying the Black-Scholes option price by the departure probability. This ignores the possibility that executive departure is less likely when stock price is high, and thus is correlated with the stock price. We show that this correlation implies a substantial increase in option values. A similar situation occurs in performance-based option packages, where the actual number of options granted depends on stock performance.